Intimacy : understanding the subtle power of human connection - Marar, Ziyad (Routledge, 2014)
The hope for intimacy lies deep within us all. That moment of feeling uniquely understood, the antidote to isolation, is what gives us value, validation and self-belief. But as Ziyad Marar shows in this fascinating and engaging study, intimacy is a tricky business. The prevalence of social media, for example, is a sign of our desire for human connection, yet is a symptom of how little we truly achieve it. Often confused with love, intimacy is in many ways more important. Marar''s investigation and celebration of this elusive but profound human experience shows how intimacy is central to a life.